Postcolonial contraventions : Cultural readings of race, imperialism and transnationalism (2003)
This book has evolved over nine years. The year 1993 saw the publication of my co-edited Colonial Discourse and Post-colonial Theory: A Reader, which was the first anthology of postcolonial cultural studies to appear in print.1 Since then the field has rapidly expanded into a major academic industry.2 Diaspora studies, black Atlantic studies, transnational studies, globalisation studies, comparative empire studies have emerged alongside and within the original field. My responses to the field’s developments are gathered here. These are a combination of literary, cultural and theoretical discussions, united by a number of critical concerns and by a desire to engage contemporary postcolonial thinkers in productive dialogue.